UK Corporate Law and Corporate Governance before 1914: a Re-interpretation - James Foreman-Peck; Leslie Hannah (European Historical Economics Society (EHES), 2015)
The consensus among legal and economic historians that British law between 1844 and 1914 provided little protection to corporate shareholders is based on formal provisions in the Companies Acts. In fact these Acts applied only to companies registered by the Board of Trade. Moreover corporate law for statutory companies was codified in the Companies Clauses Consolidation Act of 1845. We show that, while the governance rules of private companies were largely unconstrained, for most of the Victorian period most capital in quoted companies (which were mainly statutory) scored highly on the "anti-director" rights index under mandatory rules. When registered companies came to dominate stock exchanges, nearer the end of the nineteenth century, they voluntarily adopted similar rules, which professionals serving the stock exchange and IPOs recognised had advantages for raising capital. The main exception was the omission of tiered voting rules (whose record in protecting minorities was at best debatable), in favour of one-share-one vote. Unlike the prevailing consensus, our reinterpretation is consistent with evidence on the large size of the London Stock Exchange and extensive divorce of ownership from control in listed UK companies before 1914.
Keywords: K22; L51; 330; Corporate governance; anti-directors rights; voluntary regulation